Antibiotics And Bacterial Resistance: A Global Challenge That Needs To Be Addressed - Sugiah Sugiah; Fadli Fadli; Fitria Hariati; Khrisna Agung Cendekiawan (Journal of Pharmacopoeia, 2025)
This study aims to explore the global challenges faced in addressing bacterial resistance to antibiotics, which are now one of the most serious health threats in the world. This study was conducted through the Systematic Literature Review (SLR) method by searching scientific articles from various databases such as PubMed, Scopus, and Google Scholar using the keywords "antibiotic resistance", "global health", "treatment failure", and "resistance mechanisms". The articles analyzed are publications in the last 10 years, focusing on the causes of resistance, their impact on global health, and countermeasures that have been carried out. The results of the study show that antibiotic resistance is mainly caused by the inappropriate use of antibiotics in the medical and non-medical sectors, lack of distribution supervision, and lack of development of new antibiotics. To overcome this, a comprehensive approach is needed, including increasing public education and health workers, strengthening regulations, and developing alternative therapies such as phagotherapy and vaccines. Without proper treatment, antibiotic resistance can lead to infection treatment failure, increased mortality rates, and burden the global health system